Guía didáctica con metodologías activas que mejoren las clases virtuales para básica superior. - Chávez, Ana L. (2022)
The Didactic Guide with active methodologies that improve virtual classes for Upper Basic began with the selection of reference sources to substantiate theoretically the active methodologies, digital learning tools, and virtual communication platforms that were used during the period of health crisis in the national territory of Ecuador. As a general objective was proposed: Develop a didactic guide with a focus on active methodologies, by the use of innovative technological tools for the improvement of virtual classes in Higher Basic. A research methodology was designed with a survey that was applied to 23 teachers and 76 students of 8th, 9th, and 10th BGE. The most relevant results are: for the teachers, the change from the face-to-face to the virtual modality was shorty satisfactory, they eventually used digital learning tools, such as PowerPoint, YouTube, Word, and Canva, on Teams, and Zoom platforms, the students added WhatsApp. There is not always the participation and interest of students in virtual classes. The tools most used by teachers are videos, and dynamics. The majority of teachers and students are in favor of returning to attendance; and although teachers are unwilling to use digital tools, students believe that teachers should incorporate this type of technological resources in face-to- face classes. The elaboration of a Didactic Guide with active methodologies for its application in face-to-face or virtual classes of General Basic Higher Education is proposed.